(untitled)
Complexes of the type [(DIPPnacnac)MgNH(R)BH ] have been prepared (DIPPnacnac=CH(CMe)(2,6-iPr C H N) ). The following substituents R have been used: H, Me, iPr, DIPP (DIPP = 2,6-diisopropylphenyl). Complexes [(DIPPnacnac)MgNH BH ]·THF, [(DIPPnacnac)MgNH(iPr)BH ] and [(DIPPnacnac)MgNH(DIPP)BH ] were structurally characterised. The Mg amidoborane complexes decompose at a significantly higher temperature (90-110°C) than the corresponding Ca amidoborane complexes (20100°C). The complexes with the smaller R substituents (H, Me) gave a mixture of decomposition products of which one could be structurally characterised as [(DIPPnacnac)Mg (H BNMe-BH-NMe)·THF. [(DIPPnacnac)MgNH(iPr)BH ] cleanly decomposed to [(DIPPnacnac)MgH], which was characterised as a dimeric THF adduct. The amidoborane complex with the larger DIPP-substituent decomposed into a borylamide complex [(DIPPnacnac)MgN (DIPP)BH ], which was structurally characterised as its THF adduct. Bimetallic Mg amidoborane complexes decompose at lower temperatures (60-90°C) and show a different decomposition pathway. The dinuclear Mg amidoborane complexes presented here are based on DIPPnacnac units that are either directly coupled through N-N bonding (abbreviated NN) or through a 2,6-pyridylene bridge (abbreviated PYR). Crystal structures of [PYR-Mg(nBu) ], [PYR-(MgNH(iPr)BH